2020
DOI: 10.1155/2020/4518512
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Polyurethane-Based Nanocomposites Modified with Carbon Fibres and Carbon Nanotubes

Abstract: Self-healing polyurethanes (PUs) were synthesized as a matrix of nanocomposites containing two fibrous carbon components, i.e., functionalized carbon nanotubes (CNF-OH) and short carbon fibers (CF). Two types of PUs differing in the content of flexible chain segments (40% and 50%) were used. Changes in mechanical strength were analyzed to assess the ability to self-healing of PU-based matrix nanocomposites with experimentally introduced damage in the form of an incision. The healing process was activated by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Electrochemical and localised corrosion studies have revealed that bio-based PU [25,26] coatings and modified PU [27,28] showed self-healing and anti-corrosion properties. Moreover, there have been researches on development of self-healing composite coatings by incorporating different healing agents containers within PU matrix [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical and localised corrosion studies have revealed that bio-based PU [25,26] coatings and modified PU [27,28] showed self-healing and anti-corrosion properties. Moreover, there have been researches on development of self-healing composite coatings by incorporating different healing agents containers within PU matrix [29,30].…”
Section: Introductionmentioning
confidence: 99%